ICG Lymphography in a 4-week Postmortem Cadaver: Implications for a Supermicrosurgery Training Model. Issue 3 (March 2021) - Zolper, Elizabeth G.; Bekeny, Jenna C.; Fan, Kenneth L.; Tzou, Chieh-Han John; Song, David H.
Abstract : Summary: Surgical models are invaluable resources for training and for research and innovation. In the field of supermicrosurgery (SM), options for surgical models remain limited and imperfect. We report the use of a fresh, previously frozen 4-week postmortem cadaveric specimen for successful distal to proximal indocyanine green (ICG) lymphography of the upper extremity. Our technique was confirmed with handheld SPY fluorescence imaging, which visualized a clearly defined, linear lymphatic system. By outlining a straightforward, reproducible method of lymphatic mapping in cadaveric specimens, our group aims to expand the frontiers of surgical models for SM.